The design and analysist of a low cost tire endurance testing machine frame - Mohd Fadly, Nur Yakim (2007)
Testing machines are becoming increasingly important in the tire industry. Today the development period for new vehicles is less than two years. The number of sports cars and cross-country vehicles with four-wheel drive is growing and these require tires with better on-road performance as well as off-road properties. The endurance tester has been designed to determine the service life of tires. This tire testing machine enables to test the durability of the tires with a combination of internal pressure of tire, loading force and speed of rotation. Of course the impact on the tire should be way higher than in reality to reduce the time needed until the tire shows malfunctions such as buckling. The tire endurance testing machine selected Is Drum Tire Testing Machine. But, the costs for this tire testing machine found in industries are too high and expensive.